Roux-En Y Gastric Bypass Results in Long-Term Remission of Hepatocyte Apoptosis and Hepatic Histological Features of Non-alcoholic Steatohepatitis - Schneck, Anne-Sophie; Anty, Rodolphe; Patouraux, Stéphanie; Bonnafous, Stéphanie; Rousseau, Déborah; Lebeaupin, Cynthia; Bailly-Maitre, Beatrice; Sans, Arnaud; Tran, Albert; Gugenheim, Jean; Iannelli, Antonio; Gual, Philippe (Frontiers in Physiology, 2016)
The long-term effects of bariatric surgery on non alcoholic steatohepatitis (NASH), focusing on liver injury and hepatocyte apoptosis,are not well established. We here performed a longitudinal study with paired liver biopsies of 9 morbidly obese women (median BMI: 42 [38.7; 45.1] kg/m2) with NASH with a median follow-up of 55 [44; 75] months after laparoscopic Roux-en-Y gastric bypass (LRYGB) surgery. LRYGB surgery was associated with significant weight loss (median BMI loss –13.7 [–16.4; –9.5] kg/m2), improved hepatic steatosis in all patients (55.5% with total resolution), and resolution of hepatic inflammation and hepatocyte ballooning in 100% and 88.8% of cases, respectively. Alanine aminotransferase levels dropped to normal values while hepatic activated cleaved caspase 3levels strongly decreased after a median follow-up of 55 months. Hepatocyte apoptosis, as evaluated by serum caspase-generated keratin-18 fragment, improved within the first year following LRYGB and these improvements persisted for at least 55 months. LRYGB in morbidly obese patients with NASH is thus associated with a long-lasting beneficial impact on hepatic steatohepatitis and hepatocyte death.